FEG ridiculous [stupid] poems for intelligent children - Hirsch, Robin 1940- (Megan Tingley Books, Little, Brown and Company, 2002)
A collection of twenty-three poems celebrates the joy of language and includes educational and explanatory notes
Title appears with "stupid" crossed out
Keywords: Children's poetry, English; Plays on words / Juvenile literature; English poetry; Plays on words; Play on words; Kinderlyrik; Wortspiel; Englisch; Anthologie; Kinderbuch; Jugendbuch